NIKAH MUT’AH MENURUT SYIAH DAN SUNNI - Ruslan Ruslan (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
Shia and Sunni are not two schools of fiqh. These two major streams were the result of the political phenomena of their time, then spread to theology and discussing fiqh. Mut'ah marriage (contract) does not only have a syara' dimension; but also on a theological dimension. Those who reject it will not smell heaven. The basis for the obligation of mutah marriage is contained in the Qur'an sura al-Nisa: 24 and is spread in the four hadith books, especially al-Kafi. Methodologically, the quality of this hadith study is very difficult to trace because of the critical material; both naqd bathini (intreren criticism or naqd al-khariji of the Shia when the hadith is narrated by someone who is ma'shum has been judged authentic. As for sunnis with their sources being saheeh Bukhari, shahih Muslim, and Sunan Nasa'i use nasakh theory.